IDENTIFIKASI PEWARNA RHODAMIN B PADA PERONA MATA DENGAN KROMATOGRAFI LAPIS TIPIS - Indra, Febryan Feriza; Jayadi, Lukky; Ikayanti, Retno (Jurnal Insan Farmasi Indonesia, 2024)
Eyeshadow is a cosmetic that contains color pigments derived from natural/inorganic ingredients. The results of the BPOM survey conducted in 2021 to 2022 found that 16 sample products of blush on, nail polish, lip balm, eyeshadow and lipstick did not meet the requirements, containing prohibited ingredients, Rhodamine B. Considering the high use of cosmetics by the public and the report of eyeshadows that contain Rhodamine B, then it is necessary toidentify the Rhodamine B content in the eyeshadow. The aim of this study was to identify Rhodamine B in eyeshadow samples using Thin Layer Chromatography (TLC). The samples used were 4 different brands without BPOM registration numbers, consisting of 10 pallets, with pink to dark red colors. Identification was carried out using the TLC method with the mobile phase n-butanol: ethyl acetate: 25% ammonia (55:20:25). The test was carried out in 2 replications with the test results showing that 3 out of 10 samples showed the color and the Rf value that was in line with the Rf 0.63 of Rhodamine B standard. Further analysis was carried out by applying the UV light at 254 nm and 366 nm to the plate, and showed a typical fluorescence of Rhodamine B.